Upaya Guru Pendidikan Agama Islam Dalam Menerapkan Metode Role Playing Untuk Membentuk Akhlakul Karimah Pada Siswa SMP Muhammadiyah 10 SurakartaTahun Ajaran 2014/2015 - Ningsih, Setiya; , Dr. Abdullah Aly M.Ag; , Drs.Arief Wibowo, M.Ag (2016)
The aspect of moral education applied in 10 Muhammadiyah Junior High School of Surakarta particularly addressed to some students themselves are students who have problems in social interaction and discipline. The level of social interaction and discipline applied by most of the students in 10 Muhammadiyah Junior High School of Surakarta are in accordance with the vision and mission of the school but there are still some students who have problems in these two things; social interaction and discipline. The problems are typically caused by internal or external factors. The objective of the researchisto describe the effort of the implementation of role play method to create good morals of the students of 10 Muhammadiyah Junior High School of Surakarta in the academic year of 2014/2015. This research is experimental. The technique of data collection uses scale or questionnare method and also interview method. This research applies quantitative method using descriptive analysis which analyzes written data or interview and direct observation from the informen and their attitudes, so that the researcher tries to conduct the research in order to give comprehensive description. The result of the research shows that the attempt done by moral education teacher in implementing role playing method to create good morals of students of 10 Muhammadiyah Junior High School of Surakarta is effective when the method is apllied in the learning process. This method, then, can attract students' interests and motivation in their study because the process will not be monotonous and boring. Thus, role play method has a lot of innovation in learning process to both students and teacher. Therefore, role play method is one of methods that will be applied to simplify the process of learning so the process can be understood easily. Finally, the goal of learning can be reached.